Nutrient Status of Oocytes and Eggs of Muga Silkmoth Antheraea Assama as Influenced by Food Plant and Season in Terai Region of West Bengal, India - Chaudhuri, N.; Ghorai, R.; Senapati, S. K. (International Journal of Bio-resource and Stress Management, 2023)
The nutrient status of oocytes and eggs (laid in different days) of Antheraea assama Ww. varied in successive five generations with the food over seasons in Terai region of West Bengal. The nutrient contents in oocyte were found relatively lower as compared to the eggs. The concentration of protein, carbohydrate and lipid in oocytes were higher when the larvae fed on soalu (Litsaea polyantha Juss.) leaves but the FAA content was found higher in som fed one. The concentration of protein, FAA and lipid were the maximum in the eggs when the food plant was som (Machilus bombycina King. syn. Persea bombycina Kost.) but for carbohydrate it was soalu. Among the generations, the concentration of protein was the maximum in September-October (Bhodia) followed by March-April (Chotua) and being minimum in May-June (Jethua) crop. The carbohydrate concentration was the maximum in October-November (Katia) and being the minimum in May-June (Jethua) crop. The FAA concentration was higher during December-February (Jarua) in 1st day eggs and oocytes and the level was lowest in September-October (Bhodia) crop. The lipid concentration was the maximum in December-February (Jarua) crop and the minimum in March-April (Chotua) crop. The hatching % was also recorded higher in September-October (Bhodia), October- November (Katia) and March-April (Chotua) crop. During May-June, the hatching % was found to be the lowest. Therefore, it can be said that the nutrient content in oocytes and eggs and its impact on hatching was maximum in first two generations completed during September to November and decrease gradually with a peak during March-April and the lowest being found in fifth generation completed during May- June, the commercial season.